2020
DOI: 10.1111/1750-3841.15300
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Elaeagnus multiflora Thunb. fruit fermented by lactic acid bacteria inhibit SW480 human colon adenocarcinoma via induction of cell cycle arrest and suppression of metastatic potential

Abstract: Elaeagnus multiflora Thunb. (cherry silverberry, CS) is an underutilized fruit with notable phytochemical profile and biological activities. However, there are few studies on cancer inhibitory effect using fermented CS fruits. This study aimed to develop fermented CS fruits using lactic acid bacteria and investigate its anticolorectal cancer (CRC) property and phenolic composition. SW480 CRC cells were treated with aqueous extracts of CS fermented by single and coculture of Lactobacillus plantarum and L. casei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The PI3K/Akt/mTOR pathway could transmit mitotic signals to cyclins and promote the progression of cells from the G1 phase to the S phase (Lizardo, Cho, Lee, Won, & Seo, 2020). The results of the study by Wu et al revealed that A549 cells were arrested in the G0 phase and cell growth was inhibited, which was achieved by treatment with an Akt inhibitor (Yumei, Yumei, Peng, & Hua, 2016), and that p‐Akt can activate transcription factors to promote cell progression to the S phase (Xigang & Ling, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt/mTOR pathway could transmit mitotic signals to cyclins and promote the progression of cells from the G1 phase to the S phase (Lizardo, Cho, Lee, Won, & Seo, 2020). The results of the study by Wu et al revealed that A549 cells were arrested in the G0 phase and cell growth was inhibited, which was achieved by treatment with an Akt inhibitor (Yumei, Yumei, Peng, & Hua, 2016), and that p‐Akt can activate transcription factors to promote cell progression to the S phase (Xigang & Ling, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SW480 CRC cells were treated with aqueous extracts of cherry silverberry fermented by mixed strains (L. plantarum and L. casei); compared with unfermented cherry silverberry extract and controls, fermented cherry silverberry extract exhibited the most potent tumor suppressor properties at 25-50 µg/mL. The anticancer properties of cherry silverberry extract were found to be related to the increased contents of epigallocatechin gallate, rutin, naringin, and quercetin after fermentation [126]. The main active ingredient in plant ginseng is saponins.…”
Section: Anti-tumor Functionmentioning
confidence: 99%
“…The protective effect of milk against cancer with a synergistic combination of Lactobacillus gasseri 505 and melon berry leaf extract that have potential anticancer characteristic against colorectal cancer [45]. L. casei and L. plantarum were utilized as a functional food and ingredient exhibited the most potent anticancer effect on human colon adenocarcinoma by regulating apoptotic proteins [46].Prebiotics are those molecules/fibres which help probiotics grow in the human gut. Mixing Leuconostoc mesenteroides and Lactobacillus sakei in kimchi fermentation produced variable percentages of mannitol, acetic acid, and lactic acid [47].…”
Section: Nutraceuticals From Bacterial Originmentioning
confidence: 99%